2019
DOI: 10.1016/j.cimid.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and characteristics of community-acquired pneumonia in an influenza epidemic period

Abstract: A B S T R A C TPurpose: The etiology of community-acquired pneumonia (CAP) in hospital patients is often ambiguous due to the limited pathogen detection. Lack of a microbiological diagnosis impairs precision treatment in CAP. Methods: Specimens collected from the lower respiratory tract of 195 CAP patients, viruses were measured by the Single-plex real-time PCR assay and the conventional culture method was exploited for bacteria. Results: Among the 195 patients, there were 46 (23.59%) pure bacterial infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
1
0
0
1
Order By: Relevance
“…In our study, the overall prevalence of bacterial isolates was 38.7%, consistent with studies from Ethiopia reported by Temesgen et al [1], Adhanom et al [12], Regasa et al [31,32], and findings from Nigeria reported by Salami et al [44]. However, the finding in this study was higher than the findings from Brazil, China, and the USA reported by Assunção et al [5], Lin et al [45], and Carugati et al [46], respectively, while it was lower than the findings in other parts of Ethiopia and elsewhere [10,21,33,34,[47][48][49]. e inconsistency might be explained as real prevalence variations or methodological differences.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the overall prevalence of bacterial isolates was 38.7%, consistent with studies from Ethiopia reported by Temesgen et al [1], Adhanom et al [12], Regasa et al [31,32], and findings from Nigeria reported by Salami et al [44]. However, the finding in this study was higher than the findings from Brazil, China, and the USA reported by Assunção et al [5], Lin et al [45], and Carugati et al [46], respectively, while it was lower than the findings in other parts of Ethiopia and elsewhere [10,21,33,34,[47][48][49]. e inconsistency might be explained as real prevalence variations or methodological differences.…”
Section: Discussionsupporting
confidence: 90%
“…Da mesma forma, na pandemia de Influenza em 2009, relacionou-se a pneumonia bacteriana com a letalidade dos casos (Barnes et al, 2019). Em pesquisa realizada na China, onde foram coletadas amostras de escarro de 195 pacientes com pneumonia adquirida na comunidade (PAC), internados no First Affiliated Hospital of Shantou University Medical College, durante epidemia de Influenza de janeiro a agosto de 2016, foi identificada A. baumannii como a bactéria mais frequentes (Lin et al, 2019).…”
Section: Introductionunclassified